Contribution to the knowledge of the genus Lithostege Hübner, 1825 (Lepidoptera, Geometridae) with confirming the bona species status of Lithostege amseli Wiltshire, 1967 and descriptions of two new species from Central Asia - Hossein Rajaei; Igor Kostjuk (Journal of Insect Biodiversity and Systematics, 2024)
Recent research on the genus Lithostege Hübner, 1825 has raised questions about the taxonomic status of Lithostege amseli Wiltshire, 1967. Examination of the recently rediscovered holotype confirms its validity as a distinct species. Furthermore, we have now clarified the taxonomy of Lithostege amoenata Christoph, 1885, a species that was previously misinterpreted. Additionally, two new species of the genus Lithostege from Afghanistan and Tajikistan are described here (L. hausmanni sp. n. and L. viidaleppi sp. n.). The wing patterns and genitalia structures of the discussed species are illustrated, and their diagnostic characteristics are discussed.